Implementasi Kebiasaan Membaca Terhadap Prestasi Belajar Siswa Sekolah Dasar - Sagita Natalia Balalembang (Prodi PGSD Unsultra, 2023)
The purpose of this literature study is to examine the Implementation of Reading Habits on Elementary School Students' Learning Achievement. This research method uses qualitative research by reviewing literature to describe facts or circumstances related to the implementation of reading habits on elementary school students' learning achievement. The results of this literature study can be concluded that with the implementation of consistent reading habits and supported by the role and strategies of various teachers, students will be able to improve their literacy skills, which directly impacts their learning achievement in various subjects